ZIF-ZnCoO / NF electrode and preparation method and application thereof
By preparing ZIF-ZnCoO/NF electrodes using hydrothermal reaction and coordination reaction methods on foam metal substrates, the problems of structural density and insufficient catalytic site density caused by high temperature oxidation are solved, and electrocatalytic hydrogen evolution performance with high specific surface area and catalytic activity are achieved.
Patent Information
- Application Number
- CN202411987697.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-31
AI Technical Summary
In the prior art, when preparing bimetallic ZnCoO electrode materials by high temperature oxidation method, the structure is dense, the specific surface area is low and the catalytic site density is insufficient, which affects the effective performance of catalytic performance.
By combining hydrothermal reaction and coordination reaction, a thin film with a ZIF structure was directly grown on the foam metal substrate. The film was closely combined with the foam metal substrate by annealing to prepare a ZIF-ZnCoO/NF electrode.
The specific surface area and catalytic activity of ZIF-ZnCoO/NF electrodes are significantly improved, and the problems of structural density and insufficient catalytic site density in traditional methods are avoided, and the electrocatalytic hydrogen evolution performance is improved.
Smart Images

Figure CN119776905A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of electrochemistry, and in particular to a ZIF-ZnCoO / NF electrode and a preparation method and application thereof. Background Art
[0002] Faced with increasingly severe energy and environmental pollution problems, humans need cleaner energy to cope with the impending crisis. As a promising solution, water electrolysis to produce hydrogen has attracted widespread attention and discussion. Currently, the most efficient catalysts for water electrolysis to produce hydrogen are precious metal catalysts represented by platinum, palladium and rhodium, but their scarcity and high cost have severely limited the large-scale application of electrocatalytic hydrogen evolution technology.
[0003] ZnCoO usually has a nanostructure, and this nanoscale size gives it unique physical and chemical properties. For example, the one-dimensional structure of ZnCoO nanorods can shorten the lithium ion diffusion path, while the porous structure can suppress the volume strain during the charge and discharge process, thereby improving its electrochemical performance.
[0004] At present, the high-temperature oxidation method is mainly used to prepare bimetallic ZnCoO electrode materials. Although this method can prepare the required materials, the structure of the bimetallic ZnCoO electrode material tends to be dense during the high-temperature treatment process, resulting in a relatively low specific surface area of the obtained bimetallic ZnCoO electrode material, which in turn makes the catalytic site density insufficient, affecting the effective performance of the catalytic performance of the bimetallic ZnCoO electrode material. Summary of the invention
[0005] In view of the problems existing in the prior art, the present invention provides a ZIF-ZnCoO / NF electrode and a preparation method and application thereof. The present invention dissolves a soluble zinc salt, a soluble cobalt salt, urea and ammonium fluoride in water to obtain a mixed solution, and places a foam metal substrate in the mixed solution for hydrothermal reaction to obtain a precursor ZnCo(CO3)OH / NF; then the precursor ZnCo(CO3)OH / NF is placed in a dimethylimidazole aqueous solution for coordination reaction, and annealing is performed to obtain a ZIF-ZnCoO / NF electrode. The present invention utilizes a method combining hydrothermal reaction and coordination reaction to directly grow a thin film having a ZIF structure on a foam metal substrate, and after annealing, the thin film is tightly combined with the foam metal substrate, which not only significantly improves the specific surface area and catalytic activity of the ZIF-ZnCoO / NF electrode, but also overcomes the problems of dense structure, low specific surface area and insufficient catalytic site density when preparing bimetallic ZnCoO electrode materials by traditional high-temperature oxidation method.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is:
[0007] The first object of the present invention is to provide a method for preparing a ZIF-ZnCoO / NF electrode, comprising the following steps:
[0008] S1, dissolving a soluble zinc salt, a soluble cobalt salt, urea and ammonium fluoride in water to obtain a mixed solution; wherein Zn 2 + 、Co 2+ 、F - The molar ratio to urea is 1:1 to 4:8:16; the catalytic center in the electrocatalytic hydrogen evolution reaction is mainly cobalt ions, and zinc ions mainly play a structural support and synergistic role, so the molar amount of cobalt ions is slightly greater than the molar amount of zinc ions.
[0009] S2, immersing the foam metal substrate in the mixed solution for hydrothermal reaction, during the hydrothermal reaction, urea and water are thermally decomposed to generate ammonia water, making the mixed solution weakly alkaline, and at the same time, urea is thermally decomposed to obtain carbonate ions. Under weakly alkaline conditions, ammonium fluoride is used as a directing agent. Under the guiding effect of ammonium fluoride, Zn 2+ and Co 2+ It reacts with carbonate ions and hydroxide ions in the mixed solution to form basic carbonate, which is attached to the foam metal. - Embedded into the layered structure of basic nickel carbonate to obtain the precursor ZnCo(CO3)OH / NF.
[0010] S3, after the precursor ZnCo(CO3)OH / NF is placed in a dimethylimidazole aqueous solution, the dimethylimidazole molecules and the Zn on the surface of the precursor ZnCo(CO3)OH / NF are 2+ and Co 2+ During the coordination reaction, the lone pair of electrons of the nitrogen atom in the dimethylimidazole molecule reacts with the Zn on the surface of the precursor ZnCo(CO3)OH / NF. 2+ The empty orbitals of the ions interact with each other to form coordination bonds, constructing a film with a ZIF structure. After annealing, the film is tightly bonded to the foam metal substrate to obtain a ZIF-ZnCoO / NF electrode.
[0011] Preferably, the mass concentration of dimethylimidazole in the dimethylimidazole aqueous solution is 0.06 g / mL to 0.8 g / mL; during the reaction, the amount of dimethylimidazole is much greater than the molar amount of zinc and cobalt, which promotes the coordination reaction to proceed continuously and positively, thereby improving the yield.
[0012] Preferably, the hydrothermal reaction conditions are: stirring at 110° C. to 140° C. for 4 h to 8 h.
[0013] Preferably, the coordination reaction conditions are: standing at room temperature for 1 h to 5 h ;If the time is too short, the coordination reaction will not be complete, and the ZIF structure film will be redissolved in the dimethylimidazole solution during the time process, resulting in a decrease in the yield.
[0014] Preferably, the soluble zinc salt is selected from zinc nitrate or zinc chloride, and the soluble cobalt salt is selected from cobalt nitrate or cobalt chloride.
[0015] Preferably, the annealing treatment conditions are: heating to 250° C. to 350° C. at 2° C. / min and annealing for 2 h.
[0016] Preferably, the foam metal substrate is selected from foam nickel, foam titanium or foam copper; wherein foam nickel has a three-dimensional skeleton structure, can provide a larger deposition site, and has good stability.
[0017] The second object of the present invention is to provide a ZIF-ZnCoO / NF electrode prepared by the above preparation method.
[0018] Preferably, in the ZIF-ZnCoO / NF electrode, a thin film having a ZIF structure is attached to the metal foam, and the thin film having the ZIF structure is a nanosheet-shaped ZIF-ZnCoO, and there are protruding ZIF-ZnCoO nano-spherical particles on the surface of the nanosheet.
[0019] The third object of the present invention is to provide the use of the above ZIF-ZnCoO / NF electrode in preparing a negative electrode for catalytic hydrogen evolution reaction.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] 1. The present invention provides a method for preparing a ZIF-ZnCoO / NF electrode, comprising dissolving a soluble zinc salt, a soluble cobalt salt, urea and ammonium fluoride in water to obtain a mixed solution; in the mixed solution, Zn 2+ 、Co 2+ 、F - The molar ratio of Zn to urea is 1:1 to 4:8:16; the foam metal substrate is immersed in the mixed solution for hydrothermal reaction. During the hydrothermal reaction, urea and water are thermally decomposed to generate ammonia water, making the mixed solution weakly alkaline. At the same time, urea is thermally decomposed to obtain carbonate ions. Under weakly alkaline conditions, ammonium fluoride is used as a directing agent. Under the directing effect of ammonium fluoride, Zn 2+ and Co 2+ It reacts with carbonate ions and hydroxide ions in the mixed solution to form basic carbonate, which is attached to the foam metal. -The precursor ZnCo(CO3)OH / NF was obtained by embedding it into the layered structure of basic nickel carbonate and maintaining the stability of the layered structure. This layered structure helps to form a more loose and porous electrode material, further preventing the densification of the ZIF-ZnCoO / NF electrode structure. The precursor ZnCo(CO3)OH / NF was placed in a dimethylimidazole aqueous solution, and the dimethylimidazole molecules interacted with the Zn on the surface of the precursor ZnCo(CO3)OH / NF. 2+ and Co 2+ A coordination reaction occurs to construct a film with a ZIF structure. This ZIF structure is a three-dimensional porous crystal form, which gives the ZIF-ZnCoO / NF electrode an extremely high specific surface area and rich porosity. After annealing treatment, the film is tightly bonded to the foam metal substrate. The ZIF-structured film makes the transition metal catalytic sites evenly distributed, effectively avoiding the problem of agglomeration of metal catalytic sites in the traditional high-temperature oxidation preparation process, and obtaining a ZIF-ZnCoO / NF electrode.
[0022] 2. The ZIF-ZnCoO / NF electrode of the present invention presents a regular and orderly three-dimensional crystal structure, which provides a sufficient specific surface area for the ZIF-ZnCoO / NF electrode, and in the electrocatalytic hydrogen evolution reaction, Co 2+ As the main catalytic center, Zn 2+ This synergistic effect further improves the activity of the catalytic sites of the ZIF-ZnCoO / NF electrode, promotes the penetration of the electrolyte and the efficient transport of ions, and makes the ZIF-ZnCoO / NF electrode show higher catalytic performance in the process of hydrogen production by water electrolysis.
[0023] 3. The ZIF-ZnCoO / NF electrode of the present invention exhibits higher catalytic activity and stability in the catalytic hydrogen evolution reaction. The electrocatalytic hydrogen evolution performance test results show that the ZIF-ZnCoO / NF electrode has a very outstanding hydrogen evolution performance. 2 The overpotential at the current density is only 0.3V, and the charge transfer impedance is 35Ω, showing a fast charge transfer characteristic. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a morphology diagram of the ZIF-ZnCoO / NF electrode prepared in Example 4 of the present invention, wherein: Figure 1 Figure a is the morphology of the ZIF-ZnCoO / NF electrode in Example 4 at a lower magnification. Figure 1 Figure b is the ZIF-ZnCoO / NF electrode morphology of Example 4 at a higher rate.
[0025] Figure 2The X-ray diffraction patterns of the ZnCo-1-1 / NF precursor, ZIF-ZnCo1-1 / NF precursor and ZIF-ZnCoO-1-1 / NF electrode of Example 4 of the present invention are shown in FIG. Figure 2 Figure a is the X-ray diffraction pattern of ZnCo-1-1 / NF precursor. Figure 2 Figure b is the X-ray diffraction pattern of ZIF-ZnCo-1-1 / NF precursor. Figure 2 Figure c is the X-ray diffraction pattern of the ZIF-ZnCoO-1-1 / NF electrode.
[0026] Figure 3 The LSV curve and EIS test diagram of the precursor ZnCo(CO3)OH / NF prepared in Examples 1 to 4 of the present invention, wherein: Figure 3 Figure a is the LSV curve of the precursor ZnCo(CO3)OH / NF prepared in Examples 1 to 4 at various ratios. Figure 3 Figure b is the EIS test graph of various ratios of the precursor ZnCo(CO3)OH / NF prepared in Examples 1 to 4.
[0027] Figure 4 The LSV curves and EIS test diagrams of the ZIF-ZnCo / NF precursors prepared in Examples 1 to 4 of the present invention are shown in FIG. Figure 4 Figure a is the LSV curve of the ZIF-ZnCo / NF precursor obtained in Examples 1 to 4. Figure 4 Figure b is the EIS test graph of the ZIF-ZnCo / NF precursor prepared in Examples 1 to 4.
[0028] Figure 5 The LSV curves and EIS test diagrams of the ZIF-ZnCo / NF electrodes prepared in Examples 1 to 4 of the present invention are shown in FIG. Figure 5 Figure a is the LSV curve of each ratio of ZIF-ZnCo / NF electrodes prepared in Examples 1 to 4. Figure 5 Figure b is the EIS test graph of the ZIF-ZnCo / NF electrodes prepared in Examples 1 to 4. DETAILED DESCRIPTION
[0029] The technical solution of the present invention will be clearly and completely described below in combination with the data in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0031] In the prior art, high temperature oxidation is the main method for preparing bimetallic ZnCoO electrode materials. Although this method can successfully synthesize the desired electrode material, the high temperature treatment process causes the structure of the bimetallic ZnCoO electrode material to become relatively dense, resulting in a relatively low specific surface area of the obtained bimetallic ZnCoO electrode material, which in turn makes its catalytic site density insufficient, affecting the effective performance of the catalytic performance of the bimetallic ZnCoO electrode material.
[0032] In view of the above technical defects, the present invention provides a method for preparing a ZIF-ZnCoO / NF electrode, comprising dissolving a soluble zinc salt, a soluble cobalt salt, urea and ammonium fluoride in water to obtain a mixed solution; in the mixed solution, Zn 2+ 、Co 2+ 、F - The molar ratio of Zn to urea is 1:1 to 4:8:16; the foam metal substrate is immersed in the mixed solution for hydrothermal reaction. During the hydrothermal reaction, urea and water are thermally decomposed to generate ammonia water, making the mixed solution weakly alkaline. At the same time, urea is thermally decomposed to obtain carbonate ions. Under weakly alkaline conditions, ammonium fluoride is used as a directing agent. Under the directing effect of ammonium fluoride, Zn 2+ and Co 2+ It reacts with carbonate ions and hydroxide ions in the mixed solution to form basic carbonate, which is attached to the foam metal. - The precursor ZnCo(CO3)OH / NF was embedded into the layered structure of basic nickel carbonate to obtain the precursor ZnCo(CO3)OH / NF. The precursor ZnCo(CO3)OH / NF was placed in a dimethylimidazole aqueous solution, and the dimethylimidazole molecules and the Zn on the surface of the precursor ZnCo(CO3)OH / NF were 2+ and Co 2+ A coordination reaction occurs to construct a film with a ZIF structure, and after annealing, the film is tightly combined with the foam metal substrate to obtain a ZIF-ZnCoO / NF electrode.
[0033] The present invention combines dimethyl imidazole with Zn on the surface of the precursor. 2+ and Co 2+A coordination reaction occurs to form a film with a ZIF structure. This ZIF structure is a three-dimensional porous crystal morphology, which significantly increases the specific surface area of the ZIF-ZnCoO / NF electrode and enriches its pore structure; at the same time, under the guidance of the directing agent ammonium fluoride, the ZIF-ZnCoO / NF electrode presents a regular and orderly arrangement, providing sufficient specific surface area for the ZIF-ZnCoO / NF electrode, effectively avoiding the problem of low specific surface area caused by the dense structure of the traditional high-temperature oxidation method for preparing bimetallic ZnCoO electrode materials.
[0034] In terms of insufficient catalytic site density, the porosity of ZIF structured films and foamed metal substrates provides more active sites for catalytic reactions. 2+ As the main catalytic center, Zn 2+ The synergistic effect further improves the activity of the catalytic sites of the ZIF-ZnCoO / NF electrode.
[0035] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0036] Example 1
[0037] A method for preparing a ZIF-ZnCoO / NF electrode comprises the following steps:
[0038] S1. Take the nickel foam (NF) out of the containing box, cut it into a rectangle of 1 cm×3 cm, put it in deionized water and clean it with an ultrasonic cleaner for 10 seconds, then take it out and dry it at 60° C. for use.
[0039] S2. Weigh 0.22g of Zn(NO3)2, 0.44g of Co(NO3)2, 0.22g of ammonium fluoride, and 0.9g of urea and dissolve them in 60mL of deionized water. Stir continuously for 10min at room temperature to obtain a mixed solution. Transfer the mixed solution into a 100mL reactor and place NF into the mixed solution. Then place the reactor in an electric constant temperature blast drying oven, keep it at 120℃ for 6h, cool it to room temperature, wash it alternately with deionized water and ethanol, and then vacuum dry it at 60℃ for 12h to obtain the precursor ZnCo(CO3)OH / NF, which is recorded as ZnCo-1-2 / NF.
[0040] S3. Dissolve 1.25 g of dimethylimidazole in 20 mL of deionized water, mix well to obtain a dimethylimidazole aqueous solution, let the precursor ZnCo(CO3)OH / NF stand in the dimethylimidazole aqueous solution for 3 hours, then take it out and wash it, and then vacuum dry it at 60°C for 6 hours to obtain a ZIF-ZnCoO / NF precursor.
[0041] S4. The ZIF-ZnCoO / NF precursor was placed in a tube furnace and annealed at 300° C. for 2 h to obtain a ZIF-ZnCoO / NF electrode.
[0042] Example 2
[0043] A method for preparing a ZIF-ZnCoO / NF electrode is the same as the method of Example 1, except that the molar ratio of Zn(NO3)2 to Co(NO3)2 in S2 is replaced from 1:2 to 1:4, comprising the following steps:
[0044] S1. Take the nickel foam (NF) out of the containing box, cut it into a rectangle of 1 cm×3 cm, put it in deionized water and clean it with an ultrasonic cleaner for 10 seconds, then take it out and dry it at 60° C. for use.
[0045] S2. Weigh 0.22g of Zn(NO3)2, 0.85g of Co(NO3)2, 0.22g of ammonium fluoride, and 0.9g of urea and dissolve them in 60mL of deionized water. Stir continuously for 10min at room temperature to obtain a mixed solution. Transfer the mixed solution into a 100mL reactor and place NF into the mixed solution. Then place the reactor in an electric constant temperature blast drying oven, keep it at 120°C for 6h, cool it to room temperature, wash it alternately with deionized water and ethanol, and then vacuum dry it at 60°C for 6h to obtain the precursor ZnCo(CO3)OH / NF, which is recorded as ZnCo-1-4 / NF precursor.
[0046] S3. Dissolve 1.25 g of dimethylimidazole in 20 mL of deionized water, mix well to obtain a dimethylimidazole aqueous solution, let the precursor ZnCo(CO3)OH / NF stand in the dimethylimidazole aqueous solution for 3 hours, then take it out and wash it, and then vacuum dry it at 60°C for 6 hours to obtain a ZIF-ZnCoO-1-4 / NF precursor.
[0047] S4. Place the ZIF-ZnCoO / NF precursor in a tube furnace and anneal at 300°C for 2h to obtain a ZIF-ZnCoO-1-4 / NF electrode.
[0048] Example 3
[0049] A method for preparing a ZIF-ZnCoO / NF electrode is the same as the method for preparing the electrode in Example 1, except that the molar ratio of Zn(NO3)2 to Co(NO3)2 in S2 is replaced from 1:2 to 3:4, comprising the following steps:
[0050] S1. Take the nickel foam (NF) out of the containing box, cut it into a rectangle of 1 cm×3 cm, put it in deionized water and clean it with an ultrasonic cleaner for 10 seconds, then take it out and dry it at 60° C. for use.
[0051] S2. Weigh 0.22g of Zn(NO3)2, 0.28g of Co(NO3)2, 0.22g of ammonium fluoride, and 0.9g of urea and dissolve them in 60mL of deionized water. Stir continuously for 10min at room temperature to obtain a mixed solution. Transfer the mixed solution into a 100mL reactor and place NF into the mixed solution. Then place the reactor in an electric constant temperature blast drying oven, keep it at 120℃ for 6h, cool it to room temperature, wash it alternately with deionized water and ethanol, and then vacuum dry it at 60℃ for 6h to obtain the precursor ZnCo(CO3)OH / NF, which is recorded as ZnCo-3-4 / NF precursor.
[0052] S3. Dissolve 1.25 g of dimethylimidazole in 20 mL of deionized water, mix well to obtain a dimethylimidazole aqueous solution, let the precursor ZnCo(CO3)OH / NF stand in the dimethylimidazole aqueous solution for 3 hours, then take it out and wash it, and then vacuum dry it at 60°C for 6 hours to obtain the precursor ZnCo(CO3)OH / NF, which is recorded as ZIF-ZnCoO-3-4 / NF precursor.
[0053] S4. Place the ZIF-ZnCoO / NF precursor in a tube furnace and anneal at 300°C for 2h to obtain a ZIF-ZnCoO-3-4 / NF electrode.
[0054] Example 4
[0055] A method for preparing a ZIF-ZnCoO / NF electrode is the same as the method for preparing the electrode in Example 1, except that the molar ratio of Zn(NO3)2 to Co(NO3)2 in S2 is replaced from 1:2 to 1:1, comprising the following steps:
[0056] S1. Take the nickel foam (NF) out of the containing box, cut it into a rectangle of 1 cm×3 cm, put it in deionized water and clean it with an ultrasonic cleaner for 10 seconds, then take it out and dry it at 60° C. for use.
[0057] S2. Weigh 0.22g of Zn(NO3)2, 0.21g of Co(NO3)2, 0.22g of ammonium fluoride, and 0.9g of urea and dissolve them in 60mL of deionized water. Stir continuously for 10min at room temperature to obtain a mixed solution. Transfer the mixed solution into a 100mL reactor and place NF into the mixed solution. Then place the reactor in an electric constant temperature blast drying oven, keep it at 120℃ for 6h, cool it to room temperature, wash it alternately with deionized water and ethanol, and then vacuum dry it at 60℃ for 6h to obtain the precursor ZnCo(CO3)OH / NF, which is recorded as ZnCo-1-1 / NF precursor.
[0058] S3. Dissolve 1.25 g of dimethylimidazole in 20 mL of deionized water, mix well to obtain a dimethylimidazole aqueous solution, let the precursor ZnCo(CO3)OH / NF stand in the dimethylimidazole aqueous solution for 3 h, then take it out and wash it, and then vacuum dry it at 60°C for 6 h to obtain the ZIF-ZnCoO-1-1 / NF precursor.
[0059] S4. Place the ZIF-ZnCoO / NF precursor in a tube furnace and anneal at 300°C for 2h to obtain a ZIF-ZnCoO-1-1 / NF electrode.
[0060] Depend on Figure 1 It can be observed from Figure a that except for a few cracks and defects, the whole is uniform. It is composed of uniform nanosheet ZIF structure film, which provides abundant active sites and contact area for catalysis. Figure 1 Figure b shows that the surface of the ZIF-ZnCoO / NF electrode is distributed with nanospheres of different sizes and similar shapes. The surface of these nanospheres is rough, which significantly increases the specific surface area, thereby providing more active sites. The diameter of the nanospheres is between 100nm and 200nm. In addition, the surface of the ZIF-ZnCoO / NF electrode is accompanied by partial agglomeration, indicating that the structure between the nanospheres is tightly connected, forming a good pore gap structure, which not only enhances the performance stability of the ZIF-ZnCoO / NF electrode, but also provides unlimited potential for increasing its capacity.
[0061] observe Figure 2 Figure a shows that the peaks at diffraction angles of 45°, 50°, and 70° are compared with the (001), (101), and (110) crystal planes of the PDF#51-1331 standard card of Co(OH)2, indicating that the ZnCo-1-1 / NF precursor prepared in Example 4 contains Co(OH)2, and the diffraction peaks therein are partially offset, which is due to the fact that the Zn element enters the structure of the ZnCo-1-1 / NF precursor in the form of doping. Figure 2In Figure b, combined with the standard card, the ZIF-67 standard PDF card indicated by the red line has corresponding peaks at diffraction angles of 13°, 18°, and 32.5°, indicating that the ZIF-ZnCo1-1 / NF precursor exists in a metal-organic framework structure. Figure 2 Figure c in Figure 3 is combined with the standard card, and by comparing the diffraction angles of 32°, 38°, and 45° peaks corresponding to the PDF#43-1003 standard card (101), (100), and (100) crystal planes of the ZIF-ZnCoO-1-1 / NF electrode prepared in Example 4, it is shown that the ZIF-ZnCoO-1-1 / NF electrode prepared in Example 4 has a partial shift in the peaks because Zn enters the prepared ZIF-ZnCoO-1-1 / NF electrode in the form of doping. Figure 2 The results in Figures a, b and c show that the precursor ZnCo(CO3)OH / NF, ZIF-precursor ZnCo(CO3)OH / NF and ZIF-ZnCoO / NF electrodes were prepared in sequence by hydrothermal method.
[0062] The precursor ZnCo(CO3)OH / NF, ZIF-precursor ZnCo(CO3)OH / NF, and ZIF-ZnCo / NF electrodes prepared in Examples 1 to 4 were used as working electrodes, Hg / HgO was used as a reference electrode, and a platinum sheet was used as a counter electrode. One end of the working electrode, the reference electrode, and the counter electrode were placed in a 1 mol / L KOH solution, and the other ends were electrically connected to an electrochemical workstation. The test results are shown below:
[0063] Depend on Figure 3 It can be observed from Figure a that under the same current density condition, ZnCo-1-1 / NF has the lowest potential. As the ratio of Zn to Co in the precursor ZnCo gradually decreases, that is, the ratio of Co increases, the activity of the ZnCo / NF with increased ratio is greater than that of the ZnCo / NF without increased ratio, that is, the activity of ZnCo-1-4 / NF is the highest, and the activity of ZnCo-1-1 / NF is the lowest. Figure 3 It can be observed from Figure b that the impedance radius of ZnCo-1-4 / NF is the smallest, and the impedance radius of ZnCo-1-2 / NF, ZnCo-3-4 / NF and ZnCo-1-1 / NF increases successively, indicating that ZnCo-1-4 / NF has the smallest impedance in the catalytic hydrogen evolution reaction process and its performance is also the best.
[0064] Depend on Figure 4It can be observed from Figure a that under the same current density condition, the potential of the ZIF-ZnCo-1-1 / NF precursor is the lowest. As the ratio of Zn to Co in the ZnCo precursor gradually decreases, that is, the ratio of Co increases, the activity of the ZnCo precursor with an increased Co ratio is greater than that of the ZnCo precursor without an increased Co ratio, that is, the activity of the ZnCo-1-4 / NF precursor is the highest, and the activity of the ZnCo-1-1 / NF precursor is the lowest. Figure 4 It can be observed from Figure b that the impedance radius of ZnCo-1-1 / NF precursor is the smallest, and the impedance radius of ZnCo-1-4 / NF precursor, ZnCo-1-2 / NF precursor and ZnCo-3-4 / NF precursor increases successively, indicating that ZnCo-1-1 / NF precursor has the smallest impedance during the catalytic hydrogen evolution reaction and its performance is also the best.
[0065] Depend on Figure 5 It can be observed from Figure a that under the same current density condition, the potential of ZIF-ZnCoO-1-1 / NF is the lowest. As the ratio of Zn to Co in the precursor ZnCo gradually decreases, that is, the ratio of Co increases, the activity of the ZnCo material with increased Co ratio is greater than that of the ZnCo material without increased Co ratio, that is, the activity of ZnCo-1-4 / NF is the highest, and the activity of ZnCo-1-1 / NF is the lowest. Figure 5 It can be observed from Figure b that the impedance radius of ZIF-ZnCoO-3-4 / NF is the smallest, and the impedance radius of ZIF-ZnCoO-1-4 / NF, ZIF-ZnCoO-1-2 / NF and ZIF-ZnCoO-1-1 / NF increases successively, indicating that ZnCo-3-4 / NF has the smallest impedance in the catalytic hydrogen evolution reaction process and its performance is also the best.
[0066] Combination Figure 3 Figure a in Figure 4 a in and Figure 5 Figure a shows that under the same current density, when the ratio of Zn and Co is fixed, the potential of the ZIF-ZnCoO / NF electrode is the lowest, which indicates that the ZIF-ZnCoO / NF electrode has the highest catalytic efficiency. And compared with the CoZn / NF precursor and the ZIF-precursor ZnCo(CO3)OH / NF, it is found that with the preparation process of the ZIF-ZnCoO / NF electrode, the specific surface area of the ZIF-ZnCoO / NF electrode is gradually increasing, and the catalytic hydrogen evolution energy of the ZIF-ZnCoO / NF electrode is gradually increasing, and finally shows the best catalytic activity. Combined with Figure 3 b in Figure 4 b in and Figure 5Figure b shows that the precursor ZnCo(CO3)OH / NF and ZIF-precursor ZnCo(CO3)OH / NF prepared in Examples 1 to 4 have arc shapes, and the starting points of the arcs are close, indicating that the solution impedances of the precursor ZnCo(CO3)OH / NF and ZIF-precursor ZnCo(CO3)OH / NF prepared in Examples 1 to 4 are similar. At the same time, compared with the precursor ZnCo(CO3)OH / NF and ZIF-precursor ZnCo(CO3)OH / NF, the ZIF-ZnCoO / NF electrode exhibits a smaller charge transfer resistance, indicating that the ZIF-ZnCoO / NF electrode has a faster electron transfer rate, confirming its faster OER kinetics. In addition, by comparing Figure 4 Figure b and Figure 3 Figure b shows that the ZIF-ZnCoO / NF electrode has a smaller charge transfer impedance value than the precursor ZnCo(CO3)OH / NF, which indicates that the formation of bimetallic oxides greatly reduces the charge transfer impedance of the ZIF-ZnCoO / NF electrode in the catalytic reaction. This process improves the catalytic efficiency of the ZIF-ZnCoO / NF electrode.
[0067] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0068] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for preparing a ZIF-ZnCoO / NF electrode, characterized in that: The following steps are involved: Dissolve soluble zinc salt, soluble cobalt salt, urea and ammonium fluoride in water to obtain a mixed solution; in the mixed solution, Zn 2+ 、Co 2+ 、F - The molar ratio with urea is 1:1 to 4:8:16; The foam metal substrate is immersed in the mixed solution and subjected to a hydrothermal reaction. During the hydrothermal reaction, urea and water are thermally decomposed to generate ammonia water, making the mixed solution weakly alkaline. At the same time, urea is thermally decomposed to obtain carbonate ions. Under weakly alkaline conditions, ammonium fluoride is used as a directing agent. Under the directing effect of ammonium fluoride, Zn 2+ and Co 2+ It reacts with carbonate ions and hydroxide ions in the mixed solution to form basic carbonate, which is attached to the foam metal. - It is embedded into the layered structure of basic nickel carbonate to obtain the precursor ZnCo(CO3)OH / NF; The precursor ZnCo(CO3)OH / NF was placed in a dimethylimidazole aqueous solution. The dimethylimidazole molecules and the Zn on the surface of the precursor ZnCo(CO3)OH / NF 2+ and Co 2+ A coordination reaction occurs to construct a film with a ZIF structure, and after annealing, the film is tightly combined with the foam metal substrate to obtain a ZIF-ZnCoO / NF electrode.
2. The method for preparing a ZIF-ZnCoO / NF electrode according to claim 1, characterized in that: The mass concentration of dimethylimidazole in the dimethylimidazole aqueous solution is 0.06 g / mL to 0.8 g / mL.
3. The method for preparing a ZIF-ZnCoO / NF electrode according to claim 1, characterized in that: The conditions of the hydrothermal reaction are: stirring at 110°C to 140°C for 4h to 8h.
4. The method for preparing a ZIF-ZnCoO / NF electrode according to claim 1, characterized in that: The conditions for the coordination reaction are: standing at room temperature for 1 h to 5 h.
5. The method for preparing a ZIF-ZnCoO / NF electrode according to claim 1, characterized in that: The annealing conditions are: annealing at 250°C to 350°C for 2h.
6. The method for preparing a ZIF-ZnCoO / NF electrode according to claim 1, characterized in that: The foam metal is selected from foam nickel, foam titanium or foam copper.
7. A ZIF-ZnCoO / NF electrode prepared by the preparation method according to any one of claims 1 to 6.
8. The ZIF-ZnCoO / NF electrode according to claim 7, characterized in that: In the ZIF-ZnCoO / NF electrode, a thin film with a ZIF structure is attached to the foam metal. The thin film with the ZIF structure is a nanosheet-like ZIF-ZnCoO, and there are protruding ZIF-ZnCoO nano-spherical particles on the surface of the nanosheet.
9. Use of the ZIF-ZnCoO / NF electrode according to claim 8 in preparing a negative electrode for catalytic hydrogen evolution reaction.
Citation Information
Patent Citations
CoZn-LDHs-ZIF@C composite structure material with electrocatalytic water total decomposition performance as well as preparation method and application
CN110075853A
Molybdenum disulfide@ZIF-67@CoO-NF composite material as well as synthesis method and application thereof
CN113130216A
Hydrogen production catalyst as well as preparation method and application thereof
CN114855186A
Preparation method and application of Fe-doped CoS / NF three-dimensional self-supporting electrocatalyst for full-pH water electrolysis hydrogen production
CN116855982A